HIJAB: KONSEP GENDER SPACE DALAM ARSITEKTUR VERNAKULAR ACEH - Fakriah, Nurul (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
Rumoh Aceh is part of vernacular architecture in Aceh which the society is believed has strong bound to Islamic belief. This study aims to investigate the relationship between Islam and space pattern production in Rumoh Aceh, especially in gender space production. The result shows that hijab concept is the concept that is used in gender space production based on Islamic values refers to Islamic sources.